The original line has the equation given by \( y = 3x + 2 \).
To translate the line one unit to the right and two units up, we need to adjust the equation accordingly.
-
Shifting one unit to the right: When a line is translated one unit to the right, we replace \( x \) with \( x - 1 \). So the equation becomes: \[ y = 3(x - 1) + 2 = 3x - 3 + 2 = 3x - 1. \]
-
Shifting two units up: To shift the line two units up, we simply add 2 to the entire equation: \[ y = 3x - 1 + 2 = 3x + 1. \]
Thus, the equation of the new line after the translation is: \[ \boxed{y = 3x + 1}. \]